Sustained reduction in rotavirus-coded hospitalizations in children aged <5 years after introduction of self-financed rotavirus vaccines in Japan - Masayuki Kobayashi; Makoto Miyazaki; Akira Ogawa; Masatoshi Tatsumi (Human Vaccines & Immunotherapeutics, 2020)
This is an extension of our previous study, which evaluated the incidence of seasonal rotavirus gastroenteritis (RVGE) hospitalizations in children aged <5 years from 2009 to 2015 in Japan. Here, we evaluated the incidence of RVGE hospitalizations in children aged <10 years during the rotavirus season (January‒June) from 2009 to 2017 in Japan, before and after the monovalent and pentavalent rotavirus vaccines were introduced in November 2011 and July 2012, using the same health insurance claims database and study methods. In children aged <5 years, the incidence of RVGE hospitalizations greatly declined in 2014 after vaccine introduction, consistent with our previous findings, and the decline was sustained until 2017. However, in children aged ≥5‒<10 years, no apparent trend for a continuous decline in RVGE hospitalizations was observed during the study period. Improved RV vaccination coverage may lead to a further reduction in severe RVGE in Japan.